Environmentally assessing a Product-Service System: Bearings & maintenance in the pulping industry - Solheim, Jon (My University, 2013)
Compelling evidence tells us we need to change consumption and production patterns to allow for ecosystems not to collapse in the near future. This is true also for industrial actors and the products they manufacture and sell to be incorporated in other systems, manufacturing other products. Not only must manufacturing processes be radically more effective, it seems also that there is a need to consume less material goods and focus more on the utility of products then the products per se. Product-Service Systems, PSS, are put forward as a tool with this aim. The study uses a case scenario where a bearing manufacturer and a pulp mill engage in a bearing maintenance contract, identified as being a PSS. The study aims at assessing the effectiveness of that PSS. It is done in two steps; the first is a custom environmental assessment of the pulp over time for the duration of the maintenance contract so far. The second is a more in-depth, qualitative analysis of the contract structure, which is compared to literature findings on PSS that support environmental goals. The results render information on both the effectiveness of the PSS and some improvement potentials. Trends illustrate a worsening of environmental performance of the pulp production over time, but also some promising areas open for improvement. They could be addressed by internalizing the costs of products, setting explicit environmental goals and making cultural change efforts in the bearing manufacturer organisation.
Keywords: Energi; Hållbar utveckling; Geovetenskap och miljövetenskap; Naturresursteknik; Miljöbioteknik; Industriell bioteknik; Energy; Sustainable Development; Earth and Related Environmental Sciences; Environmental Engineering; Environmental Biotechnology; Industrial Biotechnology